Change, technology and higher education: are universities capable of organisational change? - Stephen Marshall (Association for Learning Technology, 2010)
Technology and change are so closely related that the use of the word innovation seems synonymous with technology in many contexts, including that of higher education. This paper contends that university culture and existing capability constrain such innovation and to a large extent determine the nature and extent of organisational change. In the absence of strong leadership, technologies are simply used as vehicles to enable changes that are already intended or which reinforce the current identity. These contentions are supported by evidence from e-learning benchmarking activities carried out over the past five years in universities in the United States, the United Kingdom, Australia and New Zealand.